2021
DOI: 10.7717/peerj.11277
|View full text |Cite
|
Sign up to set email alerts
|

The impact of functional excess of footwear on the foot shape of 7-year-old girls and boys

Abstract: Background Properly fitted shoes can support the development of growing feet and prevent problems and pathologies, not only in childhood, but also in adulthood. This points to the need to conduct research on the impact of shoe fitting on the structure of the foot in order to raise awareness and importance of this problem, to enable proper decisions regarding the purchase and use of shoes. The aim of this study was to analyze indoor footwear fit and its impact on foot structure in 7-year-old scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(36 reference statements)
1
2
2
Order By: Relevance
“…The children with too-short shoes and close-fitting shoes had a higher average of HVA of three and two degrees of HVA regarding to correct-fitting and too-long shoes, respectively. However, unlike other studies the observed relationship between the fit length of the shoes and HVA was not significant [9,10,14].…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…The children with too-short shoes and close-fitting shoes had a higher average of HVA of three and two degrees of HVA regarding to correct-fitting and too-long shoes, respectively. However, unlike other studies the observed relationship between the fit length of the shoes and HVA was not significant [9,10,14].…”
Section: Discussioncontrasting
confidence: 94%
“…The results of our study show that girls had on average more pronounced HVA than boys although without significant differences, and that in general, older children had more pronounced angles than younger ones. This finding is in disagreement with what was observed in previous studies [9,10,14]. In these studies, the relative risk for a lateral hallux deviation when wearing shoes of insufficient length was significantly higher for boys than for girls.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations